Faktor yang Mempengaruhi Kepatuhan Ibu Balita Usia 1-3 Tahun dalam Pemberian Imunisasi di Posyandu - Nurfadhillah; Tutik Agustini; Rizqy Iftitah Alam; Idelriani; Yusrah Taqiyah (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
Basic immunization services for children in Indonesia have been integrated starting from Posyandu, Puskesmas and hospitals, but the overall coverage of basic immunization is still below the target set by the government. This study aims to determine the factors that influence the compliance of mothers of toddlers aged 1-3 years in administering immunizations in Watubangga District, Kolaka Regency. This type of research used quantitative research methods with a cross-sectional study design which was carried out in the working area of ​​the Puskesmas in Watubangga District, Kolaka Regency. Sampling using probability sampling technique using simple random sampling with a total sample of 55 Ibuts. Data collection was carried out using a questionnaire. Data were analyzed using the Chi Square test at a 95% confidence level (alpha=0.05). The results of this study indicate that there is a significant effect between knowledge (p=0.000) and maternal adherence in immunization, and there is no effect between perception (p=0.571), quality of immunization services (p=0.654), number of children (p=0.771), the distance between health services (p=0.653) and maternal adherence in administering immunizations in Watubangga District, Kolaka Regency. It can be concluded that there is an effect of knowledge on maternal compliance in administering immunizations at Posyandu, Watubangga District, Kolaka Regency. Based on the research results obtained, it is hoped that health workers can be more aggressive in providing health services in the form of health education which can be carried out routinely and can also be accompanied by distribution of brochures, placing banners or billboards, especially regarding the importance of immunization in children, with the hope that all layers of society get information evenly about the immunization.